Scrutinising science : (Palgrave Macmillan, 2004)
The authors (all affiliated with the institute PREST<-->Policy Research in Engineering, Science, and Technology<-->at the U. of Manchester, UK) critically examine the policy-initiated transformation of the Government Research Establishments (GREs) of the UK, a transformation that has been based upon the ideas of the "New Public Management" concept of public administration. They assess the implications of these changes for the structure of the GREs, the nature of scientific knowledge, and the "visions" of science.